Choose Your Own Disruption: Clown, Adaptation, and Play. (November 2014) - Dicecco, Nico; Lane, Julia Helen
We ask the following: Is there anything that disappears (is ephemeral) in a scholarly text? Is it possible to foreground this ephemerality in order to write as performance rather than writing about or reading as performance? Exploring the performativity of text as well as how such textual performance interacts with clown and adaptation, we hope to enact a variety of disruptions of reader expectation, logic and flow, binaries, the academic article as a genre, and the commonly assumed reader–text relationship. Our incorporation of the gimmick of the Choose-Your-Own Adventure applies the clown's nonseriousness to the "rules" (of time, of physics, and of academic convention) that differentiate the written text from performance. Our interpretative aim in incorporating these two systems of rules is to consider how space might be opened up for the performativity of text in order to bridge what is, in many respects, an insurmountable gap.